An uncommon entity of primary ovarian fibroid: a case report - Bettaiah, Ramesh; Kurkuri, Shraddha Neminath; B. R., Vanishree; T. M., Chaithra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovarian fibroid is a rare solid benign tumor that accounts for 0.5 to 1% of all benign ovarian tumors and approximately 70 cases have been reported in literature till date. Most of these tumors are unilateral, small in size and generally occur in premenopausal women. It is usually diagnosed incidentally during pelvic examination or pathological examination after surgery. The origin of ovarian fibroid is still unresolved. We here in present a case of 31-year-old woman with primary infertility diagnosed to have right primary ovarian fibroid with an endometriotic cyst in the same ovary presenting with pain abdomen. She underwent laparoscopic tumor resection with cystectomy. Ovarian fibroid was confirmed by immunohistochemical study. Despite its rarity, ovarian fibroid should be considered in the differential diagnosis of ovarian spindle cell tumors. This is a rare case of primary ovarian fibroid with review of literature, especially highlighting the need for conservative ovary-preserving surgery in reproductive age group women.